The Regulation of Genetic Aspects of Donated Reproductive Tissue: The Need for Federal Regulation - Heled, Yaniv (Science and Technology Law Review, 2009)
It is estimated that egg and sperm donations account for more than 60,000 births every year in the United States. However, surprisingly, and despite common misconceptions, there are no federal requirements and barely any state requirements to screen and test sperm and egg donors for genetic diseases. The only nationwide standards for genetic screening and testing of donated reproductive tissue are guidelines created by professional organizations, but compliance with those guidelines is voluntary so they cannot be enforced effectively. Furthermore, the few reported cases involving children born from genetically-compromised reproductive tissue illustrate the court system’s failure to afford such children and their families the relief they need and deserve. With a continuing rise in the number of babies born each year who are conceived with donated reproductive tissue, it is necessary to create a regulatory framework requiring the screening and testing of reproductive tissue donors for genetic diseases. This article makes the case for federal regulation of the genetic aspects of donated reproductive tissue under the authority granted to the FDA by the Public Health Service Act.